Platinum-cobalt solid solution catalyst and its preparation method and application

By adsorbing organic acids and Co sources with thiol groups on the carbon black support in step by step and forming a Pt-Co catalyst with the platinum source, the problems of poor uniformity of nanoparticles and insufficient active sites are solved, and the activity and dispersion of the catalyst are improved It is suitable for oxygen reduction reaction of hydrogen fuel cell with proton exchange membrane.

CN118888770BActive Publication Date: 2024-12-24CHANGCHUN GOLD RES INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411358953.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2024-12-24
Estimated Expiration
2044-09-27

AI Technical Summary

Technical Problem

The existing Pt-Co catalysts have problems with poor nanoparticle uniformity and insufficient active sites in proton exchange membrane fuel cells, resulting in limited improvement in catalyst activity.

Method used

Step-by-step adsorption method is used to first adsorb organic acids and Co sources with thiol groups on the carbon black support, regulate pH to weak alkalinity to form Co/C support, and then adsorb and reduce the platinum source. The thiol group is bonded to Pt-Co particles. , improve the activity of the catalyst.

Benefits of technology

The uniform distribution and high activity of Pt-Co particles are achieved. The half-wave potential of the catalyst is higher than that of commercial platinum carbon catalysts, and the mass-specific activity is much higher than that of commercial platinum carbon catalysts. It is suitable for oxygen reduction reactions of proton exchange membrane hydrogen fuel cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118888770B_ABST
    Figure CN118888770B_ABST
Patent Text Reader

Abstract

The present invention provides a platinum-cobalt solid solution catalyst and a preparation method and application thereof, and relates to the field of new energy materials and application technology. The preparation method adopts a step-by-step adsorption method to prepare a PtCo / C solid solution catalyst. First, an organic acid with a thiol group is adsorbed onto a carbon carrier, and then a Co source is adsorbed, and a thiol-modified Co / C carrier is reduced to form a thiol-modified Co / C carrier, which is used as a carrier to adsorb a Pt source and reduce, and a PtCo / C solid solution catalyst is obtained after washing, drying, and grinding. The preparation method adsorbs Co source and Pt source in steps, which is conducive to the uniform distribution of Pt-Co particles. On the other hand, the thiol group is adsorbed onto the carbon carrier to increase the active sites of the carrier, and the thiol group can be bonded to the Pt-Co particles, thereby achieving anchoring of the Pt-Co particles and improving the activity of the catalyst. The Pt-Co particles in the PtCo / C solid solution catalyst prepared by the method are evenly distributed, the particle size of the Pt-Co particles is 2-6nm, and the half-wave potential and mass specific activity (mass activity) are higher than those of commercial platinum-carbon catalysts, and can be applied to the oxygen reduction reaction of proton exchange membrane hydrogen fuel cells.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of new energy materials and application technologies, and in particular to a platinum-cobalt solid solution catalyst and a preparation method and application thereof. Background Art

[0002] Proton exchange membrane fuel cell (PEMFC) is an efficient and clean energy conversion device, but the cathode reaction kinetics of fuel cells are slow, and Pt / C catalysts are usually needed to increase the reaction rate. Although commercial platinum carbon has been applied to the market, Pt as a rare precious metal leads to high cost of hydrogen fuel cells, and its activity and stability still need to be improved.

[0003] At present, researchers have used transition metals and Pt to form alloy structures of nanocatalysts to improve the utilization rate of Pt atoms. Many researchers choose to develop Pt-Co catalysts. Co atoms are embedded in the Pt lattice, causing changes in the electronic structure of platinum atoms, which is conducive to the transfer of electrons and thus improves the ORR activity of Pt.

[0004] However, the current literature mostly adopts a one-step adsorption method, in which Pt and Co are adsorbed and reduced at the same time, which makes it difficult to ensure the uniformity of nanoparticles. In order to improve the uniformity of nanoparticles, patent CN113097503A proposes a step-by-step adsorption method. Specifically, the patent discloses a method for synthesizing a proton exchange membrane fuel cell catalyst, first dispersing a Pt / C precursor in water to obtain a Pt / C precursor dispersion; mixing the dispersion with an inorganic cobalt salt in a ratio of 1:1 to obtain a mixed dispersion; then, adding NaBH 4 The aqueous solution is added dropwise to the mixed dispersion to obtain a mixed solution; the mixed solution is filtered, washed, and dried to obtain a Pt / C sample containing Co; the Pt / C sample containing Co is placed in an argon atmosphere, heated and cooled to obtain a PtCo / C alloy catalyst containing cobalt particles; the PtCo / C alloy catalyst containing cobalt particles is washed in an acid solution to obtain a PtCo / C catalyst.

[0005] This method uses a step-by-step adsorption method, first adsorbing Pt to form a Pt / C carrier, and then adsorbing Co, which can make the Pt-Co particles disperse more evenly. However, this method does not have enough active sites on the carrier, and no measures are taken to anchor the Pt-Co particles, so the degree of improvement in catalyst activity is limited. Summary of the invention

[0006] In view of the defects of the above-mentioned prior art, the purpose of the present invention is to provide a method for preparing a platinum-cobalt solid solution catalyst, which adopts a method of step-by-step adsorption of Pt and Co, first adsorbing the Co source, and adjusting the pH of the system to a weak alkaline state to facilitate the adsorption of Co by the carrier, and obtaining a Co / C carrier after reduction, which provides a good matrix for the subsequent adsorption of Pt, improves the dispersion of the catalyst, and thus improves the activity of the catalyst; and, before adsorbing the Co source, an organic acid with a thiol group is first adsorbed, the thiol group can increase the active sites of the carbon carrier and can bond with the Pt-Co particles, thereby achieving anchoring of the Pt-Co particles and improving the activity of the catalyst.

[0007] To achieve the above object, the present invention provides a method for preparing a platinum-cobalt solid solution catalyst, comprising the following steps:

[0008] S1, ultrasonically dispersing a carbon black carrier, an organic acid containing a mercapto group and deionized water, stirring for 1-3 hours to obtain a, and ultrasonically dispersing a cobalt source and ethylene glycol to obtain b;

[0009] S2, add b into a under stirring, perform ultrasonication, and stir at room temperature for 1-2h to obtain a mixed solution A;

[0010] S3, adding an ammonia solution to the mixed solution A under stirring, adjusting the pH to 5-9, ultrasonicating, and stirring at room temperature to obtain a mixed solution B;

[0011] S4, adding formaldehyde aqueous solution to the mixed solution B under stirring, ultrasonicating, stirring at room temperature to obtain a mixed solution C; refluxing in a water bath at 70-90° C. and stirring for 1-3 h, filtering, washing with deionized water, drying, and grinding to obtain a thiol-modified Co / C carrier;

[0012] In the mixed solution C, the concentration of cobalt is 0.005-0.04 g / L, the mass ratio of cobalt to carbon black carrier is 1:(1-50), the molar ratio of thiol-containing organic acid to cobalt is (1-5):1, and the volume ratio of deionized water to ethylene glycol in the solution is (1-5):1;

[0013] S5, ultrasonically dispersing the Co / C carrier and deionized water to obtain c, and ultrasonically dispersing the platinum source and ethylene glycol to obtain d;

[0014] S6, adding d to c under stirring to obtain a mixed solution D, ultrasonicating, and stirring at room temperature for 4-15h;

[0015] S7, adding formaldehyde aqueous solution to the mixed solution D under stirring, ultrasonicating, stirring at room temperature to obtain a mixed solution E; refluxing in a water bath at 70-90° C. and stirring for 1-3 h, filtering, washing with deionized water, drying, and grinding to obtain a PtCo / C catalyst;

[0016] In the mixed solution E, the concentration of platinum is 0.01-0.2 g / L, the mass ratio of platinum to carbon black carrier is 1:(1-10), and the volume ratio of deionized water to ethylene glycol in the solution is (1-5):1.

[0017] Furthermore, in step S1, the carbon black carrier is one of Ketjen black, Cabot black and acetylene black.

[0018] Furthermore, in step S1, the cobalt source is an ethylene glycol solution of one or more of cobalt nitrate hexahydrate, cobalt chloride, and cobalt sulfate.

[0019] Furthermore, in step S1, the thiol-containing organic acid is one or both of thioglycolic acid and mercaptopropionic acid.

[0020] Furthermore, in step S3, the concentration of the aqueous ammonia solution is 5wt%-30wt%.

[0021] Furthermore, in steps S4 and S7, the concentration of the formaldehyde aqueous solution is 1 g-5 g / L, and the volume is 10 ml-100 ml.

[0022] Furthermore, in step S5, the platinum source is an ethylene glycol solution of one or both of platinum nitrate and chloroplatinic acid.

[0023] The present invention also provides a platinum-cobalt solid solution catalyst, which is prepared by the above-mentioned preparation method. The Pt-Co particles in the platinum-cobalt solid solution catalyst are evenly distributed, and the particle size range of the Pt-Co particles in the platinum-cobalt solid solution catalyst is 2-6nm.

[0024] Furthermore, in the PtCo / C catalyst, the molar ratio of Pt to Co is (0.5-4):1.

[0025] The aforementioned platinum-cobalt solid solution catalyst can be used for the oxygen reduction reaction in a proton exchange membrane hydrogen fuel cell.

[0026] The beneficial effects of the present invention are:

[0027] 1. The preparation method of the platinum-cobalt solid solution catalyst provided by the present invention adopts a method of stepwise adsorption of Pt and Co, first adsorbing the Co source, and adjusting the pH of the system to a weak alkaline state to facilitate the adsorption of Co by the carrier, and obtaining a Co / C carrier after reduction, which provides a good matrix for the subsequent adsorption of Pt. Such orderly adsorption can improve the dispersibility of Pt-Co particles in the catalyst, thereby improving the activity of the catalyst;

[0028] 2. The carbon carrier first adsorbs the organic acid with thiol groups before adsorbing Co, and then directly adsorbs the Co source and reduces it to form a Co / C carrier with thiol groups. Compared with the introduction of thiol groups by carrier pretreatment, the steps of filtering, washing and drying are reduced. On the one hand, the thiol groups can increase the active sites of the carrier, change the structure and electronic properties of the active sites of the catalyst, and improve the activity of the reaction. On the other hand, after the Co / C carrier adsorbs the platinum source and is reduced, the thiol groups bond with the Pt-Co particles, achieving the anchoring of the Pt-Co particles and improving the activity of the catalyst.

[0029] 3. The platinum-cobalt solid solution catalyst prepared by the present invention has uniform distribution of Pt-Co particles and a particle size of 2-6 nm, which is suitable for oxygen reduction reaction in proton exchange membrane hydrogen fuel cells. 2 Saturated 0.1 M HClO 4 The half-wave potential in the ORR polarization curve is higher than that of a commercial platinum-carbon catalyst with a platinum content of 20%, and the mass activity ratio is also much higher than that of a commercial platinum-carbon catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The present invention provides a schematic flow chart of a method for preparing a platinum-cobalt solid solution catalyst.

[0031] Figure 2 This is the TEM image of the platinum-cobalt solid solution catalyst prepared in Example 1.

[0032] Figure 3 The platinum-cobalt solid solution catalyst prepared in Example 1 and the commercial Pt / C catalyst were mixed in O 2 Saturated 0.1 M HClO 4 ORR polarization curves in .

[0033] Figure 4 The XRD patterns of Example 1 and commercial platinum carbon (20% platinum content) are shown in FIG.

[0034] Figure 5 This is the TEM image of the platinum-cobalt solid solution catalyst prepared in Example 2.

[0035] Figure 6 This is the TEM image of the platinum-cobalt solid solution catalyst prepared in Comparative Example 2. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0037] It should also be noted that, in order to avoid obscuring the present invention due to unnecessary details, only structures and / or processing steps closely related to the scheme of the present invention are shown in the drawings, while other details that are not closely related to the present invention are omitted.

[0038] In addition, it should be noted that the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.

[0039] See also Figure 1 As shown, the present invention provides a method for preparing a platinum-cobalt solid solution catalyst, comprising the following steps:

[0040] S1, ultrasonically disperse the carbon black carrier, the organic acid containing a mercapto group and deionized water, and stir for 1-3 hours to obtain a, and ultrasonically disperse the cobalt source and ethylene glycol to obtain b.

[0041] The carbon black carrier is one of Ketjen black, Cabot black and acetylene black.

[0042] The cobalt source is an ethylene glycol solution of one or more of cobalt nitrate hexahydrate, cobalt chloride, and cobalt sulfate.

[0043] The organic acid containing a thiol group is one or more of thioglycolic acid and mercaptopropionic acid.

[0044] S2, add b into a under stirring, ultrasonicate, and stir at room temperature for 1-2h to obtain a mixed solution A.

[0045] S3, adding an aqueous ammonia solution to the mixed solution A under stirring, adjusting the pH to 5-9, ultrasonicating, and stirring at room temperature to obtain a mixed solution B.

[0046] Wherein, the concentration of the ammonia solution is 5wt%-30wt%.

[0047] S4, add formaldehyde aqueous solution to the mixed solution B under stirring, perform ultrasound, and stir at room temperature to obtain a mixed solution C; reflux and stir in a water bath at 70-90°C for 1-3h, filter, wash with deionized water, dry, and grind to obtain a thiol-modified Co / C carrier.

[0048] In the mixed solution C, the concentration of cobalt is 0.005-0.04 g / L, the mass ratio of cobalt to carbon black carrier is 1:(1-50), the molar ratio of thiol-containing organic acid to cobalt is (1-5):1, and the volume ratio of deionized water to ethylene glycol in the solution is (1-5):1.

[0049] First, a carbon black carrier is used to adsorb the organic acid containing a thiol group, and then a mixed solution of a cobalt source and ethylene glycol is added to the carbon black carrier solution; then, the pH of the system is adjusted to a weakly alkaline state, which is conducive to the adsorption of Co by the carrier, thus forming a Co / C carrier with a thiol group, and the thiol group can increase the active sites of the carrier.

[0050] S5, ultrasonically disperse the Co / C carrier and deionized water to obtain c, and ultrasonically disperse the platinum source and ethylene glycol to obtain d.

[0051] The platinum source is an ethylene glycol solution of one or both of platinum nitrate and chloroplatinic acid.

[0052] S6, adding d to c under stirring to obtain a mixed solution D, ultrasonicating, and stirring at room temperature for 4-15h;

[0053] S7, adding formaldehyde aqueous solution to the mixed solution D under stirring, ultrasonicating, stirring at room temperature, to obtain a mixed solution E; refluxing in a water bath at 70-90°C for 1-3h, filtering, washing with deionized water, drying, and grinding to obtain a PtCo / C catalyst;

[0054] In the mixed solution E, the concentration of platinum is 0.01-0.2 g / L, the mass ratio of platinum to carbon black carrier is 1:(1-10), and the volume ratio of deionized water to ethylene glycol in the solution is (1-5):1.

[0055] In steps S4 and S7, the concentration of the formaldehyde aqueous solution is 1 g-5 g / L, and the volume is 10 ml-100 ml.

[0056] A platinum source is added to the Co / C carrier solution with thiol groups, and the Co / C carrier with thiol groups is bonded with Pt-Co particles, thereby achieving anchoring of the thiol groups to the Pt-Co particles and improving the activity of the catalyst.

[0057] The platinum-cobalt solid solution catalyst prepared by the preparation method of the platinum-cobalt solid solution catalyst comprises a carbon black carrier and Pt-Co particles loaded on the carbon black carrier. The Pt-Co particles are evenly distributed and have a particle size range of 2-6 nm.

[0058] In the PtCo / C catalyst, the molar ratio of Pt to Co is (0.5-4):1.

[0059] The platinum-cobalt solid solution catalyst can be used for oxygen reduction reaction in proton exchange membrane hydrogen fuel cells.

[0060] The preparation method of the platinum-cobalt solid solution catalyst provided by the present invention is described below in conjunction with specific examples. Unless otherwise specified, the raw materials and reagents in the examples of the present application are purchased through commercial channels.

[0061] Example 1

[0062] Weigh 0.1848g of Cabot carbon black carrier, 0.028g of mercaptopropionic acid and 360ml of deionized water in a 1000ml flask, treat with ultrasound for 30min, and stir at room temperature for 2h, which is recorded as a. Then weigh 2.57ml of 0.1mol / L CoCl 2 / ethylene glycol solution and 197.4 ml ethylene glycol were placed in a beaker and ultrasonically dispersed for 20 min, which was recorded as precursor solution b.

[0063] Under stirring, the precursor solution b was added to the flask containing the carbon black carrier aqueous solution a, ultrasonicated for 10 minutes, and stirred at room temperature for 30 minutes to obtain a mixed solution A.

[0064] Add appropriate amount of ammonia solution to mixed solution A, adjust to pH=8, ultrasonicate for 10 min, stir at room temperature for 1 h, take 160 mg of 40% formaldehyde solution and dissolve it in 40 ml of deionized water, then add it to the above solution, ultrasonicate for 10 min, then stir at room temperature for 30 min, put the flask into an 80°C water bath, heat and reflux for 1.5 h, magnetic stirring rate of 400 rpm, filter, wash with deionized water 5 times, 300 ml each time, and dry at 60°C to obtain a Co / C carrier.

[0065] Weigh 100 mg of Co / C and 180 ml of deionized water in a 500 ml flask and treat with ultrasound for 30 min, which is recorded as c. Then weigh 6.9 ml of 0.0186 mol / L H 2 PtCl 6 / ethylene glycol solution, 93.1 ml of ethylene glycol was placed in a beaker and ultrasonically dispersed for 20 min, recorded as precursor solution d.

[0066] Under stirring, the precursor solution d was added to the flask containing the carbon black carrier aqueous solution c, stirred at room temperature for 4 hours, and the magnetic stirring rate was 400rpm. 80 mg of 40% formaldehyde solution was dissolved in 20ml deionized water, and then added to the above solution, ultrasonically treated for 10 minutes, then stirred at room temperature for 30 minutes, heated to reflux in a 80℃ water bath for 1.5 hours, and the magnetic stirring rate was 400rpm. Filter, wash with deionized water 5 times, 300ml each time. Dry at 60℃, grind, and obtain PtCo / C catalyst.

[0067] Figure 2 This is the TEM image of the PtCo / C catalyst prepared in this example. It can be seen that the Pt-Co particles in the PtCo / C catalyst are evenly distributed and the particle size of the Pt-Co particles is 2-6 nm.

[0068] The PtCo / C catalyst prepared in this example and the commercial Pt / C catalyst (20% platinum content) from Johnson Matthey were tested in O using an electrochemical workstation equipped with a rotating disk electrode. 2 Saturated 0.1 M HClO 4 The ORR polarization curve in Figure 3 As shown, it can be seen that the half-wave potential of the PtCo / C catalyst prepared in Example 1 is higher than that of the commercial platinum-carbon catalyst.

[0069] The catalyst obtained in Example 1 and the commercial Pt / C (20% platinum content) catalyst were characterized by XRD. The results are as follows: Figure 4 It can be seen that the peak intensity of Example 1 is higher than that of the commercial platinum-carbon catalyst, indicating that the particle crystallinity is good and the platinum-cobalt grains are larger than pure platinum. The characteristic peak of Example 1 shifts to the right relative to the commercial platinum-carbon, indicating that the dissolution of cobalt causes the lattice to shrink, proving the formation of a platinum-cobalt solid solution.

[0070] Example 2

[0071] Example 2 provides a method for preparing a platinum-cobalt solid solution catalyst, which is different from Example 1 mainly in that 0.028 g of mercaptopropionic acid in Example 1 is replaced with 0.024 g of mercaptoacetic acid.

[0072] Figure 5 This is the TEM image of the PtCo / C catalyst prepared in this example. It can be seen that the Pt-Co particles in the PtCo / C catalyst are evenly distributed and the particle size of the Pt-Co particles is 2-6 nm.

[0073] Example 3

[0074] Example 3 provides a method for preparing a platinum-cobalt solid solution catalyst, which is different from Example 1 mainly in that 0.028 g of mercaptopropionic acid in Example 1 is replaced with 0.014 g of mercaptopropionic acid and 0.012 g of thioacetic acid.

[0075] Comparative Example 1

[0076] Comparative Example 1 provides a method for preparing a platinum-cobalt solid solution catalyst, which is different from Example 1 mainly in that 0.028 g of mercaptopropionic acid in Example 1 is replaced with 0.02 g of propionic acid.

[0077] Comparative Example 2

[0078] Comparative Example 2 provides a method for preparing a platinum-cobalt solid solution catalyst by adsorbing platinum and cobalt in one step. The details are as follows:

[0079] Weigh 100 mg of Cabot carbon black carrier, 0.028 g of mercaptopropionic acid and 180 ml of deionized water in a 500 ml flask, ultrasonically treat for 10 min, and stir at room temperature for 2 h, which is recorded as a. Then weigh 7.46 ml of 0.0186 mol / L H 2 PtCl 6 / ethylene glycol solution, 1.39ml 0.1mol / L CoCl 2 / ethylene glycol solution and 91.6 ml of ethylene glycol were placed in a beaker and ultrasonically dispersed for 20 min, which was recorded as precursor solution b.

[0080] Under stirring, the precursor solution b was added to the flask a containing the carbon black carrier aqueous solution, ultrasonicated for 10 minutes, stirred at room temperature for 4 hours, and the magnetic stirring rate was 400rpm. 120mg of 40% formaldehyde solution was dissolved in 20ml of deionized water and added to the above solution, ultrasonicated for 10 minutes and then stirred for 30 minutes, and an appropriate amount of ammonia solution was added to adjust the pH to about 8, ultrasonicated for 10 minutes, and then stirred for 30 minutes. The flask was placed in an 80℃ water bath, heated and refluxed for 1.5 hours, and the magnetic stirring rate was 400rpm. Filter, wash with deionized water 5 times, 300ml each time, dry at 60℃, and grind to obtain PtCo / C catalyst.

[0081] The half-wave potential and mass specific activity (mass activity) of the PtCo / C catalysts prepared in Examples 1-3 and Comparative Examples 1-2 and a commercial platinum-carbon catalyst (20% platinum content) were tested. The test results are shown in Table 1 below.

[0082] Table 1 Catalyst electrochemical test results

[0083]

[0084] Experiments show that, under the same test system, the mass specific activity of the PtCo / C catalysts prepared in Examples 1-3 is much higher than that of commercial platinum-carbon catalysts with a platinum content of 20%.

[0085] In Comparative Example 1, the mercaptopropionic acid in Example 1 was replaced with propionic acid. The pH of the system was close, but no mercapto group was introduced, and the active sites of the carrier could not be increased, nor could the Pt-Co particles be anchored. Therefore, the mass specific activity was low.

[0086] Although mercapto groups were introduced in Comparative Example 2, platinum and cobalt were adsorbed and reduced in the liquid phase simultaneously, the formation process of platinum-cobalt Pt-Co particles was relatively chaotic, and the dispersion on the carbon support was also poor, resulting in poor catalyst activity.

[0087] Figure 6This is the TEM image of Comparative Example 2. It can be seen from the figure that the platinum source and the cobalt source are adsorbed and reduced at the same time, and the dispersion of the Pt-Co particles is not uniform enough.

[0088] Embodiment 4-5

[0089] The preparation method of the platinum-cobalt solid solution catalyst provided in Examples 4-5 is different from that in Example 1 mainly in that the types of carbon black carrier, cobalt source, and platinum source are changed, as shown in Table 2. The other operations are generally the same as in Example 1 and will not be repeated here.

[0090] Table 2

[0091]

[0092] The half-wave potential and mass activity of the PtCo / C catalyst prepared in Example 4-5 were tested. The test results are shown in Table 1 below.

[0093] Table 3

[0094]

[0095] Experiments show that Examples 4-5 can also successfully produce platinum-cobalt solid solution catalysts.

[0096] In summary, the preparation method of the platinum-cobalt solid solution catalyst provided by the present invention adopts a step-by-step adsorption method to prepare the PtCo / C solid solution catalyst. First, the thiol group and the Co source are step-by-step adsorbed onto a carbon black carrier, reduced to form a thiol-modified Co / C carrier, which is used as a carrier to adsorb the Pt source and reduce it. After washing, drying, and grinding, the PtCo / C solid solution catalyst is obtained. The preparation method adsorbs an organic acid with a thiol group before adsorbing the Co source. The thiol group can increase the active sites of the carrier and can bond with the Pt-Co particles, thereby achieving anchoring of the Pt-Co particles and improving the activity of the catalyst. The Pt-Co particles in the prepared PtCo / C solid solution catalyst are evenly distributed, the particle size of the Pt-Co particles is 2-6nm, and the mass specific activity (mass activity) is higher than that of commercial platinum-carbon catalysts, and can be used for oxygen reduction reactions in proton exchange membrane hydrogen fuel cells.

[0097] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention.

Claims

1. A method for preparing a platinum-cobalt solid solution catalyst, characterized in that: The steps include: S1, ultrasonically dispersing a carbon black carrier, an organic acid containing a mercapto group and deionized water, stirring for 1-3 hours to obtain a, and ultrasonically dispersing a cobalt source and ethylene glycol to obtain b; S2, add b into a under stirring, perform ultrasonication, and stir at room temperature for 1-2h to obtain a mixed solution A; S3, adding an ammonia solution to the mixed solution A under stirring, adjusting the pH to 5-9, ultrasonicating, and stirring at room temperature to obtain a mixed solution B; S4, adding formaldehyde aqueous solution to the mixed solution B under stirring, ultrasonicating, and stirring at room temperature to obtain a mixed solution C; Reflux in a water bath at 70-90°C with stirring for 1-3h, filter, wash with deionized water, dry, and grind to obtain a thiol-modified Co / C carrier; In the mixed solution C, the concentration of cobalt is 0.005-0.04 g / L, the mass ratio of cobalt to carbon black carrier is 1:(1-50), the molar ratio of thiol-containing organic acid to cobalt is (1-5):1, and the volume ratio of deionized water to ethylene glycol in the solution is (1-5):1; S5, ultrasonically dispersing the Co / C carrier and deionized water to obtain c, and ultrasonically dispersing the platinum source and ethylene glycol to obtain d; S6, adding d to c under stirring to obtain a mixed solution D, ultrasonicating, and stirring at room temperature for 4-15h; S7, adding formaldehyde aqueous solution to the mixed solution D under stirring, ultrasonicating, stirring at room temperature to obtain a mixed solution E; refluxing in a water bath at 70-90° C. and stirring for 1-3 h, filtering, washing with deionized water, drying, and grinding to obtain a PtCo / C catalyst; In the mixed solution E, the concentration of platinum is 0.01-0.2 g / L, the mass ratio of platinum to carbon black carrier is 1:(1-10), and the volume ratio of deionized water to ethylene glycol in the solution is (1-5):

1.

2. The method for preparing a platinum-cobalt solid solution catalyst according to claim 1, characterized in that: In step S1, the carbon black carrier is one of Ketjen black, Cabot black and acetylene black.

3. The method for preparing a platinum-cobalt solid solution catalyst according to claim 1, characterized in that: In step S1, the cobalt source is an ethylene glycol solution of one or more of cobalt nitrate hexahydrate, cobalt chloride, and cobalt sulfate.

4. The method for preparing a platinum-cobalt solid solution catalyst according to claim 1, characterized in that: In step S1, the thiol-containing organic acid is one or both of thioglycolic acid and mercaptopropionic acid.

5. The method for preparing a platinum-cobalt solid solution catalyst according to claim 1, characterized in that: In step S3, the concentration of the aqueous ammonia solution is 5wt%-30wt%.

6. The method for preparing a platinum-cobalt solid solution catalyst according to claim 1, characterized in that: In steps S4 and S7, the concentration of the formaldehyde aqueous solution is 1 g-5 g / L, and the volume is 10 ml-100 ml.

7. The method for preparing a platinum-cobalt solid solution catalyst according to claim 1, characterized in that: In step S5, the platinum source is an ethylene glycol solution of one or both of platinum nitrate and chloroplatinic acid.

8. A platinum-cobalt solid solution catalyst, prepared by the preparation method of the platinum-cobalt solid solution catalyst according to any one of claims 1 to 7, characterized in that: The Pt-Co particles in the platinum-cobalt solid solution catalyst are evenly distributed, and the particle size range of the Pt-Co particles in the platinum-cobalt solid solution catalyst is 2-6 nm.

9. The platinum-cobalt solid solution catalyst according to claim 8, characterized in that: In the PtCo / C catalyst, the molar ratio of Pt to Co is (0.5-4):

1.

10. Use of the platinum-cobalt solid solution catalyst according to claim 8, characterized in that: The platinum-cobalt solid solution catalyst is applied to the oxygen reduction reaction of a proton exchange membrane hydrogen fuel cell.